ANALISIS SWOT ATAS STRATEGI EKSPANSI RUMAH SAKIT HM DITINJAU DARI KINERJA KEUANGAN DAN NON KEUANGAN - Retta Farah Pramesti; Desi Adhariani (Politeknik Ganesha Medan, 2023)
This study aims to evaluate the expansion strategy at HM Hospital using a SWOT analysis based on its financial and non-financial performance. The theory and concepts used are Resource Based View Theory (RBV), SWOT analysis, theory of performance, and expansion. This research uses quantitative and qualitative methods based on case study analysis of HM Hospital. The results showed that the financial performance of HM Hospital based on financial ratios was still quite good in terms of liquidity, activity, solvency and investment ratios. However, in terms of profitability, it has not achieved sustainable profits and has tended to still suffer losses in the last four years. Based on non-financial performance, HM Hospital which operates distinctive of heart and internal medicine is already good in terms of buildings, technology, organization, innovation, reputation and services that focus on middle to lower patients. HM Hospital focuses on the best cost strategy to peak.competitive advantage. Based on the evaluation of financial and non-financial performance, HM Hospital can focus on four strategies, it is ST(Strength-Threat), SW(Strength-Weakness), WO(Weakness-Opportunity) and WT (Weakness-Threat). By maximizing it, HM Hospital's future expansion strategy can be growth by opening new branches in the form of clinics or hospitals and successfully being listed on the Indonesia Stock Exchange (IDX) in 2024 with careful preparation and planning.